ChemInform Abstract: Schiff Base‐Derived Homogeneous and Heterogeneous Palladium Catalysts for the Suzuki—Miyaura Reaction. Issue 17 (April 2016) - Das, Pankaj; Linert, Wolfgang
Abstract: Review: 169 refs.